Patient experience and satisfaction with remote memory assessment: Responding to clinical need in times of COVID‐19 restrictions. (31st December 2021) - Raczek, Malgorzata; Porter, Emma; Daley, Stephanie; Farina, Nicolas; Velayudhan, Latha; Abraham, Rajesh
Abstract: Background: The suspension of memory services during the COVID‐19 pandemic delayed dementia diagnosis and access to early intervention. Some services responded to the challenge by developing a remote memory assessment pathway to comply with reduced social contact measures to protect vulnerable patients. The aim of the study was to establish whether remote model is considered a satisfactory experience within the context of the COVID‐19 pandemic and to understand the factors associated with patient and carer satisfaction of remote pathway. Method: 73 participants recruited from patients referred to memory clinic in West Sussex, who were assessed over a video or telephone. Participants completed an 11‐item questionnaire capturing satisfaction across a range of elements, contextual items (the impact of the pandemic, loneliness, previous experience of using teleconference technology and diagnosis), as well as 3 dimensions from Patient Experience Questionnaire. Descriptive statistics are reported at a whole sample level, separated by patient and carer status. A hypothesis driven set of bivariate analyses (Spearman's rank) was used to understand the association between overall satisfaction and key independent factors across the whole sample. Results: 73 participants were typically older adults (M=68.5, SD=13.3) and female (n=40, 54.8%). The patient was more likely to be older, feel lonely within the past week and to have used video call software when compared to the carer (p> 0.05). Participants were generally satisfied with the remote pathway with 95.8% (n=69) agreeing or strongly agreeing with the statement "Overall, I was satisfied with the assessment". Patients and carers did not significantly differ on any satisfaction response, apart from the ease of use of technology, in which carers were more likely to find the technology easy to use (U= 432.5; p=0.01). Worry about contracting COVID and communication experience was positively associated with overall satisfaction, whilst perceived communication barriers were significantly negatively associated with overall satisfaction. Conclusions: Remote memory assessment was a positive and satisfactory experience for most patient and carers. The remote pathway should be considered as an option available during and beyond the pandemic to improve access and patient choice of assessment modality.